The Relationship Between Aortic Arch Calcification and Recurrent Stroke in Patients With Embolic Stroke of Undetermined Source—A Case-Control Study - Cai, Xiaofeng; Geng, Yu; Zhang, Sheng (Frontiers in Neurology, 2022)
Background: Aortic arch calcification (AoAC) is associated with plaque development and cardiovascular events. We aimed to estimate the predictive value of AoAC for stroke recurrence in patients with embolic stroke of undetermined source (ESUS). Methods: Consecutive patients with ESUS who were admitted to our centre between October 2019 and October 2020 and who had a 1-year follow-up of stroke recurrence were retrospectively reviewed. According to our AoAC grading scale (AGS), AoAC was classified into four grades based on chest computed tomography findings: no visible calcification (grade 0), spotty calcification (grade 1), lamellar calcification (grade 2), and circular calcification (grade 3). Results: Of the 158 patients with ESUS (age, 62.1±14.5 years; 120 males) enrolled, 24 (15.2%) had recurrent stroke within a 1-year follow-up. Cox regression analysis showed that stroke history (hazard ratio, 4.625; 95% confidence interval, 1.828–11.700, P=0.001) and AoAC (hazard ratio, 2.672; 95% confidence interval, 1.129–6.319; P=0.025) predicted recurrent stroke. AGS grade 1 was associated with a significantly higher risk of stroke recurrence than AGS grade 0 (hazard ratio, 5.033; 95% confidence interval, 1.858–13.635, P=0.001) and AGS grade 2 plus 3 (hazard ratio, 3.388; 95% confidence interval, 1.124–10.206, P=0.030). In AoAC patients, receiver operating characteristic (ROC) analysis showed that AGS had a good value in predicting stroke recurrence in patients with ESUS, with an area under curve (AUC) of 0.735 (95%CI=0.601–0.869, P=0.005).